Manajemen Pembelajaran dalam Upaya Peningkatan Capaian Mutu Nilai Ujian Nasional (UN) di MTs Negeri 1 Kebumen - Muhamad Anwarudin (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2020)
In general, the purpose of this research is to get a descriptive picture of the implementation of management that focuses on management of improving the quality of the results of the National Examination (UN) scores at MTs Negeri 1 Kebumen. By tracing the planning, implementation, evaluation. follow-up to improving the quality of National Examination (UN) scores at MTs Negeri 1 Kebumen. Research using qualitative methods. The process of collecting data for researchers, in order to better understand the following, will describe the procedure for collecting data in this study as follows: Observation, Interview, Study of Documents. Technical analysis of data in a qualitative research can be used descriptive narrative, through three paths, namely: Data reduction, Presentation data, and conclusion/verification. Based on the research findings, the authors can inform that: (1) Planning is making targets to be achieved or achieved in the future. Planning for improving the quality of education at MTs Negeri 1 Kebumen is carried out with various considerations. The planning function carried out at MTs Negeri 1 Kebumen includes setting up funding sources, madrasah resources or personnel and efforts to foster them, and curriculum development. Formulation of plans to improve the quality of education at MTs Negeri 1 Kebumen through deliberations or madrasah meetings involving the Madrasah head, teachers, staff and Madrasah committees. (2). Implementation or direction as a plan to improve the quality of education at MTs Negeri 1 Kebumen is implementation as a process of controlling educational institutions that run according to predetermined paths and reach their goals effectively and efficiently.